2014
DOI: 10.1111/bij.12409
|View full text |Cite
|
Sign up to set email alerts
|

Population differences in the structure and coloration of great tit contour feathers

Abstract: Contour feathers cover most of the avian body and play critical roles in insulation, social communication, aerodynamics, and water repellency. Feather production is costly and the development of the optimum characteristics for each function may be constrained by limited resources or time, and possibly also lead to trade‐offs among the different characteristics. Populations exposed to different environmental conditions may face different selective pressures, resulting in differences in feather structure and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…The patterns described by Gloger and Görnitz, which were based on limited and non-systematic observations, have not undergone rigorous testing and remain largely unknown. Recent studies on geographic variation of carotenoid-based colours in birds have sometimes revealed increases in intensity towards warmer, tropical regions (Baldassarre, Thomassen, Karubian, & Webster, 2013;Ford & Simpson, 1987;Gamero, Senar, Hohtola, Nilsson, & Broggi, 2015;Morales et al, 2017) in broad agreement with Gloger's predictions; although other studies (Chui & Doucet, 2009;Ford, 1963) reveal the opposite or no effects. Research on carotenoid-based colours has gone a long way since Gloger and Görnitz (Koch & Hill, 2018;, and this means that we can now put their observations in the context of our current understanding of these colours.…”
Section: Introductionsupporting
confidence: 54%
“…The patterns described by Gloger and Görnitz, which were based on limited and non-systematic observations, have not undergone rigorous testing and remain largely unknown. Recent studies on geographic variation of carotenoid-based colours in birds have sometimes revealed increases in intensity towards warmer, tropical regions (Baldassarre, Thomassen, Karubian, & Webster, 2013;Ford & Simpson, 1987;Gamero, Senar, Hohtola, Nilsson, & Broggi, 2015;Morales et al, 2017) in broad agreement with Gloger's predictions; although other studies (Chui & Doucet, 2009;Ford, 1963) reveal the opposite or no effects. Research on carotenoid-based colours has gone a long way since Gloger and Görnitz (Koch & Hill, 2018;, and this means that we can now put their observations in the context of our current understanding of these colours.…”
Section: Introductionsupporting
confidence: 54%
“…First, contour feathers were more variable within individuals (five feathers per individual) than between populations (six individuals per population), which could be due to natural variation among individuals. Second, there is no standard method for quantifying feather structure (Butler et al 2008), so it is possible that different variables in the contour feathers such as: barb angle (Butler, Rohwer, & Speidel 2008), hue values and infrared spectra (Dove et al 2007; Gamero et al 2015), or porosity (a function of barb width and spacing, Rijke 1968, 1970; Rijke & Jesser 2011), are better descriptors of insulation capacity. The methodology applied in this study was used because it was cost effective and easily adapted to an unconventional lab space.…”
Section: Discussionmentioning
confidence: 99%
“…The energetic costs associated with having suboptimal plumage could be substantial in waterfowl, as thermoregulation can account for 28% of the daily energy expenditure (McKinney & McWilliams 2005). Recent years have seen an increase of studies characterizing interpopulation variation of feather structure due to environmental variation (Middleton 1986; Broggi et al 2011; Gamero et al 2015; Koskenpato et al 2016), but few have focused on waterfowl or comparative data describing down feathers among species or populations inhabiting different environments (but see Pap et al 2017; D’alba et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…; Gamero et al . ). Producing feathers is costly and the development of optimum characteristics for each function is likely constrained by limited resources, including available amount and protein content of food (e.g.…”
Section: Introductionmentioning
confidence: 97%